Efeitos de um programa de treinamento multicomponente sobre a capacidade de desempenho físico funcional e o risco de quedas de idosos institucionalizados - Santos, Marília Leite dos (Brasil, 2022)
The aging process is a natural phenomenon that presents considerable changes in the levels of biological organization, contributing to the emergence of physical declines that lead to loss of functionality in the elderly, leading to the occurrence of numerous complications, one of the main ones being the risk of falls. . Objective: to analyze the effects of a multicomponent training program on the capacity for functional physical performance and the risk of falls in institutionalized elderly. Methods: Nine institutionalized elderly people participated in the multicomponent training group (MCT) and nine in the control group (CG). The functional tests had the short battery of functional performance (SPPB) and the assessment of the risk of falls. The training program took place in 12 weeks, with 3 weekly sessions of the multicomponent training model (TM), based on the VIVIFRAIL program. The evolution of intensity was based on the subjective perception of effort for all MT components and performed individually. The statistical analyzes used focused on estimates of the effect size of the experiment/intervention. The effect of the intervention was analyzed based on the delta percentage between MCT and CG. Results: Intervention comparisons based on percentage delta between MCT and GC showed favorable results for MCT in most variables of risk of falling and functional physical performance, in which for the 6m walking speed tests (d= -0.857 , large), Timed Up and Go (TUG) (d= -1.18, large) and standing up and sitting down 5 times (LS5X) (d= -1.13, large) there was a reduction in execution time; in the balance test, an increase was observed (d= 0.603, moderate); for the 4m walking speed test, there was a reduction in execution time (d= -0.814, large) and for the right and left handgrip strength (HGS) test ((d= -0.197) and (d= -0.33 ) trivial and small, respectively) the effects were insignificant for both groups and; the total SPPB score increased, indicating a decrease in the level of frailty (d= 0.803, large) also for the TMC. Conclusion: The multicomponent training program achieved significant post -intervention effects, being recommended to improve and/or maintain levels of functional physical performance capacity and to reduce the risk of falls in institutionalized elderly.